A simple method to improve the accuracy of non-invasive ultrasound in selecting TIA patients for cerebral angiography. Issue 11 (November 1990) - Humphrey, P; Sandercock, P; Slattery, J
Abstract : A prospective study is reported of the ability of B mode ultrasound imaging and continuous wave Doppler flow studies to detect different degrees of stenosis of the extracranial internal carotid artery (ICA) in 186 arteries in 99 patients with transient ischaemic attacks (TIA) and minor ischaemic stroke. A simple mathematical equation has been developed which combines the image and flow data to provide a single predictor of the degree of angiographic stenosis which has advantages over either ultrasonic modality used alone. The sensitivity and specificity of the predictive model in the detection of stenosis greater than or equal to 25% was 73% and 98%, of stenosis greater than or equal to 50% was 90% and 93%, of stenosis greater than or equal to 75%, 65% and 99% and occlusion 100% and 94% respectively. The principal clinical value of ultrasound screening is to spare patients with "non-significant" stenosis the risk of unnecessary angiography. Thus a simple measure of the Duplex screening tests' performance is the proportion of all strokes occurring as a complication of angiography that are avoided by changing the investigation policy from "angiograms for all carotid TIA and minor ischaemic stroke patients" to "angiograms for all patients with abnormal ultrasound results". If Duplex scanning were used to select patients most likely to have a significant abnormality on angiography, depending on the degree of stenosis to be detected, 52-85% of angiographic strokes might be avoided. If the predictive equation were used 62-88% of angiographic strokes might be avoided.